DAMPAK ANISOMETROPIA TINGGI YANG TIDAK TERKOREKSI PADA MATA DAN PENANGGULANGANNYA - Misnawati; Nisa Zakiati Umami (Jurnal Mata Optik, 2021)
Refraction error such as myopia, hypermetropia and astigmatism with a difference significant diopters are now experienced by a small part of people. That refraction error called anisometropia is caused by many things, such as predetermined at birth, trauma, and even the failure of surgery refraction. On the patient's anisometropia, refraction examination is done by using special Test FRIEND or a test Worth Four Dot. The author uses descriptive method of data libraries, including the essay from Troy E. Fannin, O.D. and Theodore Grosvenor, O.D., Ph.d., titled "Clinical Optics", about the condition of uncorrected anisometropia who has a bi-okuler vision. Essay from AK Khurana entitled "Theory And Practice Of Optics And Refraction" that is about the range of treatments to patient’s anisometropia, so they can see in binoculars vision comfortably.